Clinical Interchangeability Boundaries of Pentacam AXL WAVE in Preoperative Biometry for Cataract Surgery: An Agreement Study with IOLMaster 700 and Pentacam - Rong Zhao; Zhiyang Zhang; Suyu Wang; Ziyi Chen; Guangguang Wu; Siyuan Ding; Qin Jiang; Jiajun Li; Keran Li (Journal of Clinical Medicine, 2026)
Background/Objectives: Accurate preoperative biometry is essential for refractive cataract surgery. Pentacam AXL WAVE is an emerging multimodal platform integrating ocular biometry, anterior segment imaging, and corneal assessment, yet its interchangeability with established devices remains unclear. This study aimed to evaluate the agreement and clinical interchangeability of Pentacam AXL WAVE with IOLMaster 700 and Pentacam. Methods: This retrospective cross-sectional study compared Pentacam AXL WAVE with IOLMaster 700 and Pentacam across 175 eyes of 105 cataract patients. Interdevice agreement was evaluated using intraclass correlation coefficients, concordance correlation coefficients, and Bland–Altman analysis with multiple outlier-handling strategies; generalized estimating equations were applied to identify clinical factors associated with interdevice differences. Results: Pentacam AXL WAVE demonstrated good agreement with IOLMaster 700 and Pentacam for axial length and anterior corneal curvature parameters, but showed weaker agreement for white-to-white diameter, total keratometry, total corneal astigmatic vectors, and several extended anterior segment parameters. Fewer clinical factors explained interdevice differences versus IOLMaster 700, whereas ocular surface or corneal abnormalities, refractive status, and cataract characteristics were associated with greater differences versus Pentacam. Conclusions: These findings indicate that Pentacam AXL WAVE has parameter-specific interchangeability boundaries and can meet some routine biometric needs; however, for eyes requiring high refractive precision or presenting with complex ocular conditions, interpretation should be based on the agreement characteristics of individual parameters.